Cool infographics : effective communication with data visualization and design - Krum, Randy (Indianapolis, Indiana : John Wiley & Sons, Inc., 2014)
Research shows that visual information is more quickly and easily understood, and much more likely to be remembered. This innovative book presents the design process and the best software tools for creating infographics that communicate. Including a special section on how to construct the increasingly popular infographic resume, the book offers graphic designers, marketers, and business professionals vital information on the most effective ways to present data.
-- The science of infographics -- Online infographics -- Infographics and SEO -- Infographic resumes -- Internal confidential infographics -- Designing infographics -- Design resources.
Includes bibliographical references and index.
Keywords: Computer graphics; Charts, diagrams, etc. -- Design; Information visualization; Visual communication; Web sites -- Design